2011
DOI: 10.1037/a0024571
|View full text |Cite
|
Sign up to set email alerts
|

The buffering effect of resilience on depression among individuals with spinal cord injury: A structural equation model.

Abstract: Findings provide support for the resilience model and suggests characteristics of resilience "buffer" the perceptions of stress on depressive symptoms. The resilience model may be useful to guide clinical interventions designed to improve the mental health of individuals with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
161
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(188 citation statements)
references
References 81 publications
14
161
2
6
Order By: Relevance
“…1,6,8 Indeed the present study found a similar incidence (58%) of at least moderate resilience in a community sample to that reported by inpatient samples with SCI. 1,6 These findings therefore suggest that psychological adaptation to SCI may prevail in the longer term, despite the challenges associated with community living.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…1,6,8 Indeed the present study found a similar incidence (58%) of at least moderate resilience in a community sample to that reported by inpatient samples with SCI. 1,6 These findings therefore suggest that psychological adaptation to SCI may prevail in the longer term, despite the challenges associated with community living.…”
Section: Discussionsupporting
confidence: 69%
“…Further large-scale research would allow more advanced analyses, such as structural equation modelling, to better estimate the causal relationship between these variables. 1 Finally, the reliance on self-report measures of psychological outcome, which are considered to be subjective, presented a testing bias. 14 Future SCI research should therefore incorporate clinicianbased ratings, consistent with recommendations for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations